Help-seeking for cognitive problems in older adults without dementia: A systematic review - Nikki L. Hill (Elsevier, 2021)
Introduction: Understanding the help-seeking decision-making process in older adults experiencing cognitive problems is needed to improve early identification of cognitive impairment. The purpose of this systematic review was to determine what factors influence whether community-dwelling older adults without dementia seek help for cognitive problems. Methods: We conducted a mixed-methods systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A literature search was conducted in PubMed, CINAHL, PsycINFO, Web of Science, and ProQuest Dissertations and Theses Global in June 2020. Quality appraisal was conducted using the Mixed Methods Appraisal Tool. A narrative synthesis was used to integrate findings across studies. Results: Eighteen articles met eligibility criteria. All were cross-sectional studies, including nine quantitative, eight qualitative, and one containing quantitative and qualitative components. Factors that facilitated help-seeking were problem intensity, social support, valuing early detection, having a family history of dementia, and positive views of the healthcare system. Factors that detracted from help-seeking were normalizing cognitive problems, attributing problems to psychosocial causes, and not perceiving a benefit to disclosing cognitive problems. Discussion: The decision to seek help for cognitive problems is influenced by a variety of factors. Our review suggests these differ in older adults without dementia compared to previous reviews of help-seeking for a dementia diagnosis. Given the importance of early detection of cognitive impairment to improve long-term outcomes, intervention development based on the factors we identified has important implications for older adults’ cognitive health.